PERENCANAAN STRUKTUR APARTEMEN ALAM INDAH TEMANGGUNG - Zainul Miftahuddin; Desiman Sihaloho; Himawan Indarto; Bambang Pardoyo (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Structure design of Alam Indah Apartment designed with SNI 2847-2013 and SNI 1726-2012, Alam Indah Apartment building structures was included in Seismic Design Criteria Type D with high seismic risk level, so that the planning system used method with a Special Moment Resisting Frame System (Sway-special). The structure design of the apartment has a symmetrical shape configuration , so when an earthquake happens the possibility of buildings rotation is almost zero. it caused by the center of mass and the center of rigidity was located in a single point , so it is not necessary dilatation and calculations can be reviewed based on two dimensions with the help of structures software. The foundation that used in this building is a bore pile foundation.